Mirrored stainless steel substrate provides improved signal for Raman spectroscopy of tissue and cells. (29th July 2016) - Lewis, Aaran T.; Gaifulina, Riana; Isabelle, Martin; Dorney, Jennifer; Woods, Mae L.; Lloyd, Gavin R.; Lau, Katherine; Rodriguez‐Justo, Manuel; Kendall, Catherine; Stone, Nicholas; Thomas, Geraint M.
Abstract : Raman spectroscopy (RS) is a powerful technique that permits the non‐destructive chemical analysis of cells and tissues without the need for expensive and complex sample preparation. To date, samples have been routinely mounted onto calcium fluoride (CaF2 ) as this material possesses the desired mechanical and optical properties for analysis, but CaF2 is both expensive and brittle and this prevents the technique from being routinely adopted. Furthermore, Raman scattering is a weak phenomenon and CaF2 provides no means of increasing signal. For RS to be widely adopted, particularly in the clinical field, it is crucial that spectroscopists identify an alternative, low‐cost substrate capable of providing high spectral signal to noise ratios with good spatial resolution. Results show that these desired properties are attainable when using mirrored stainless steel as a Raman substrate. When compared with CaF2, data show that stainless steel has a low background signal and provides an average signal increase of 1.43 times during tissue analysis and 1.64 times when analyzing cells. This result is attributed to a double‐pass of the laser beam through the sample where the photons from the source laser and the forward scattered Raman signal are backreflected and retroreflected from the mirrored steel surface and focused towards collection optics. The spatial resolution on stainless steel is at least comparable to that on CaF2 and it is not compromised by the reflection of the laser. Steel is a fraction of the cost of CaF2 and the reflection and focusing of photons improve signal to noise ratios permitting more rapid mapping. The low cost of steel coupled with its Raman signal increasing properties and robust durability indicates that steel is an ideal substrate for biological and clinical RS as it possesses key advantages over routinely used CaF2 . © 2016 The Authors. Journal of Raman Spectroscopy Published by John Wiley & Sons Ltd. Abstract : The optical properties of stainless steel and its suitability for tissue and cell analysis using Raman spectroscopy were investigated. In comparison to CaF2, data show that stainless steel has a lower background signal and provides an average signal increase of 1.43 times during tissue analysis and 1.64 times when analyzing cells. The low cost of steel coupled with its Raman signal increasing properties and robust durability indicates that steel is an ideal substrate for biological and clinical Raman spectroscopy.